2019
DOI: 10.3390/polym11111841
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Light-degradation Behavior and Antibacterial Activity of Polypropylene/ZnO Nanoparticles Fibers

Abstract: Herein, ZnO nanoparticles (NPs) were synthesized using zinc acetate and an amino hyperbranched polymer. The methods of transmission electron microscope (TEM) and X-ray Diffraction (XRD) were applied to the characterization of ZnO NPs. Polypropylene (PP)/ZnO fiber was prepared using 1–5 wt% ZnO NPs via melt spinning. The ultraviolet light (UV)-degradation behavior, antibacterial activity and mechanical properties of PP fibers were characterized. The PP fiber filled with ZnO NPs presents better mechanical proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 31 publications
1
7
0
1
Order By: Relevance
“…However, little research has as yet been performed on the comfort and antibacterial durability of ZnO NPs antibacterial textiles, and this should be the research direction in the future. [66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][86][87][88][89]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, little research has as yet been performed on the comfort and antibacterial durability of ZnO NPs antibacterial textiles, and this should be the research direction in the future. [66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][86][87][88][89]…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that the composite fiber displayed significant antibacterial effects against the two species of bacteria, concluding that the effect was related to the content of ZnO NPs, increasing with the increased ZnO NPs concentration. Zhang et al 67 synthesized ZnO NPs(C) using zinc acetate and an amino hyperbranched polymer, and then prepared polypropylene (PP)/ZnO fiber by melt spinning method. It was observed that the fibers displayed excellent antibacterial activity against E. coli and S. aureus.…”
Section: Preparation Of Zno Np Antibacterial Fibersmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous article, we have reviewed the cytotoxic effects of ZnO nanostructures on mammalian cells [67]. As mentioned, ZnO NPs are widely used in cosmetics, suncreams, UV-absorbing packaging films and fabrics for food and medical textile applications, as well as therapeutic agents for cancer treatment [42][43][44][45][46]67]. In addition, ZnO NPs have also been added to animal (e.g., chicken) feed to promote the growth performance of the animals [319].…”
Section: Red Blood Cellsmentioning
confidence: 99%
“…Besides, silver material is expensive, and the manufacturing process of silver antibacterial agents is complicated. ZnO is another inorganic antibacterial agent, which has attracted broad interest because of high‐temperature resistance, no migration, low cost, 9 no color change in high temperature, photocatalysis and UV shielding, 12,13 especially the safety properties to human. It is recognized as a bio‐safe material 14 .…”
Section: Introductionmentioning
confidence: 99%